Teachers' training: an empirical study on training needs and digital skills - Samuele Calzone; Claudia Chellini (Firenze University Press, 2016)
Starting from the results of an empirical research on digital skills and training needs of Italian teachers involved in the National Operational Programme 2007-2013 "Skills for Development" (ESF), this paper debates the teachers' expertise in order to identify their training needs. The research is focused on four areas of interest: the perception of self-efficacy as unexpressed need, the obstacles that prevent the well-being using the teaching methodology and digital technology, the behaviour related to the use of technology in classroom and the training need expressed by teachers. La formazione del personale docente: un'indagine empirica sul fabbisogno formativo e le competenze digitali A partire da un'indagine sul fabbisogno formativo e le competenze digitali del personale docente coinvolto nel PON 2007-2013 "Competenze per lo sviluppo" (FSE), il presente lavoro intende esplorare l'expertise del personale docente al fine di intercettare il suo fabbisogno formativo. Sono stati individuati quattro ambiti di analisi: la percezione della self-efficacy (bisogno inespresso), gli ostacoli che impediscono di sentirsi "a proprio agio" con metodologie didattiche e tecnologie digitali, il comportamento relativo all'uso delle ICT in classe e il bisogno formativo espresso.